Changes in sugar, salt, and fat intake among obese adults: cohort study - Shabrina, Erfin; Briawan, Dodik; Ekayanti, Ikeu; Riyadina, Woro (Alma Ata University Press, 2022)
ABSTRAK Latar Belakang: Asupan gula, garam, dan lemak yang berlebih merupakan salah satu faktor risiko terjadinya obesitas dan penyakit tidak menular. Perubahan asupan gula, garam, dan lemak pada orang dewasa dengan kasus obesitas baru belum diteliti di Indonesia.Tujuan: Menganalisis pola asupan dan besaran perubahan asupan gula, garam, lemak pada orang dewasa obese selama dua tahun pemantauan. Metode: Desain pada penelitian ini yaitu studi longitudinal dengan menggunakan data sekunder dari Studi Kohor Faktor Resiko Penyakit Tidak Menular oleh Kementerian Kesehatan Republik Indonesia. Subjek pada penelitian ini yaitu penyandang obesitas baru sebesar 138 subjek. Nilai cut-off obesitas yang digunakan dalam penelitian yaitu IMT ≥25.00 kg/m2. Asupan gula, garam, dan lemak diperoleh dari food recall 1x24 jam dan FFQ. Pola asupan gula, garam, dan lemak dikategorikan menjadi meningkat atau menurun berdasarkan perbandingan asupan pada akhir penelitian dengan asupan GGL di T2 (tertile sedang) pada awal penelitian. Besar perubahan asupan gula, garam, dan lemak adalah selisih asupan gula, garam, dan lemak subjek penelitian di dua tahun pengamatan.Hasil: Mayoritas penyadang obesitas yaitu perempuan dengan rentang usia 35-44 tahun dan mempunyai kadar LDL yang tergolong tinggi. Adanya perubahan pada asupan gula, garam, dan lemak pada penyandang obesitas yang meningkat secara signifikan khususnya pada gula, dan lemak. Besar perubahan asupan gula, garam, dan lemak pada orang dewasa obese sebesar 10.5 g (p<0.05), 0.02 g (p>0.05), dan 10.7 g (p<0.05) selama dua tahun. Asupan pangan sumber gula, garam lemak seperti kue manis, minuman berpemanis, dan minuman sachet dengan penambahan gula, makanan kaleng, kecap, dan gorengan serta daging juga meningkat selama dua tahun pemantauan.Kesimpulan: Asupan gula, garam, dan lemak pada orang dewasa yang obesitas cenderung meningkat, dan kemungkinan besar dapat meningkatkan prevalensi obesitas dan penyakit tidak menular di Indonesia. KATA KUNCI: dewasa; asupan gula-garam-lemak; obesitas; perubahan asupan; studi longitudinalABSTRACTBackground: Excessive intake of sugar, salt, and fat (SSF) is a risk factor for obesity and non-communicable diseases. Changes in sugar, salt, and fat intake in adults with new obesity cases have not been studied in Indonesia.Objective: To analyze dietary trajectories and sugar, salt, and fat intake changes in obese adults.Methods: The design of this study was a longitudinal study using secondary data from the Study on Non-Communicable Disease Risk Factors by the Ministry of Health of the Republic of Indonesia. The subjects in this study were 138 subjects with obesity. The obesity cut-off value used in the study was BMI 25.00 kg/m2. Sugar, salt, and fat intake were obtained from food recall 1x24 hours and FFQ. The dietary trajectories of sugar, salt, and fat intake were categorized as increasing or decreasing based on the comparison of intake at the end of the study with the intake of SSF at T2 (medium tertile) at the beginning of the study. The change in the intake of sugar, salt, and fat was the difference in the subjects' intake of sugar, salt, and fat in the two years of observation.Results: The majority of obese adults were women aged 35-44 years and had high LDL levels. There was a change in the intake of sugar, salt, and fat, which increased significantly, especially sugar and fat. Changes in sugar, salt, and fat intake in obese adults were 10.5 g (p<0.05), 0.02 g (p>0.05), and 10.7 g (p<0.05) for two years. Intake of food sources of sugar, salt, and fat such as sweet food, sugar-sweetened drinks, instant powder drink with added sugar, canned food, soy sauce, fried foods, and meat also increased during the two years of monitoring.Conclusion: The intake of sugar, salt, and fat in obese adults tend to increase and is likely to increase the prevalence of obesity and non-communicable diseases in Indonesia. KEYWORDS: adult; sugar-salt-fat intake; obesity; dietary behaviour changes; longitudinal study